Functional 3-Dimensional Retinal Organoids: Technological Progress and Existing Challenges - Fathi, Meimanat; Ross, Cody T.; Hosseinzadeh, Zohreh (Frontiers in Neuroscience, 2021)
Stem cell scientists have developed methods for the self-formation of artificial organs, often referred to as organoids. Organoids can be used as model systems for research in multiple biological disciplines. Yoshiki Sasai’s innovation for deriving mammalian retinal tissue from in vitro stem cells has had a large impact on the study of the biology of vision. New developments in retinal organoid technology provide avenues for in vitro models of human retinal diseases, studies of pathological mechanisms, and development of therapies for retinal degeneration, including electronic retinal implants and gene therapy. Moreover, these innovations have played key roles in establishing models for large-scale drug screening, studying the stages of retinal development, and providing a human model for personalized therapeutic approaches, like cell transplants to replace degenerated retinal cells. Here, we first discuss the importance of human retinal organoids to the biomedical sciences. Then, we review various functional features of retinal organoids that have been developed. Finally, we highlight the current limitations of retinal organoid technologies and discuss directions of future research.